Implementation of USB in Embedded Systems Based on ARM Microprocessor - Li, Xin Li (Applied Mechanics and Materials, 2014)
S3C4510B is a cost-effective 16/32 bit RISC microcontroller based on Ethernet application system, and ISP1161 is a chip which is designed to implement USB protocol in an embedded system. Here, we design and implement embedded systems USB with ISP1161 chip based on ARM microprocessor S3C4510B. This paper describes the basic working principle of ISP1161 chip and hardware design of the system, and presents the software implementation process of USB in embedded systems.